2006
DOI: 10.1093/ajcn/83.4.835
|View full text |Cite|
|
Sign up to set email alerts
|

Chronic cigarette smoking is associated with diminished folate status, altered folate form distribution, and increased genetic damage in the buccal mucosa of healthy adults

Abstract: Chronic smoking is associated with a lower systemic status of several B vitamins, reduced oral folate, and changes in folate form distribution in the mouth. However, the cytologic damage that is evident in the mouths of smokers does not correlate with oral folate status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
75
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(91 citation statements)
references
References 48 publications
14
75
2
Order By: Relevance
“…In the controls, the highest levels of in vitro BPDE-induced DNA adducts in current smokers followed by former smokers and never smokers we observed are consistent with the previous observation that smokers are significantly more sensitive to genotoxic challenges and thus have more DNA or chromosome damage than never smokers (17). Although smoking itself may have caused the formation of adducts in lymphocytic DNA, the in vivo smokinginduced DNA adduct levels were usually 100 to 1,000 times lower than the in vitro induced adduct levels observed in our previous (5) and current studies.…”
Section: Discussionsupporting
confidence: 92%
“…In the controls, the highest levels of in vitro BPDE-induced DNA adducts in current smokers followed by former smokers and never smokers we observed are consistent with the previous observation that smokers are significantly more sensitive to genotoxic challenges and thus have more DNA or chromosome damage than never smokers (17). Although smoking itself may have caused the formation of adducts in lymphocytic DNA, the in vivo smokinginduced DNA adduct levels were usually 100 to 1,000 times lower than the in vitro induced adduct levels observed in our previous (5) and current studies.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that smoking is associated with reduced levels of vitamins including B12, which is required for synthesis of S-adenyl-methionine. 20 This might be one factor causing the association of hypomethylation and smoking, but will require further study. Subset analysis within the tumor group also showed an association of alcohol use with hypomethylation, although it is difficult to separate tobacco and alcohol effects as they tend to be confounding characteristics in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…A separate publication, which describes the relationships between micronuclei and onecarbon nutrients, contains some of the data on BMC micronuclei and the dietary intake of macronutrients (36).…”
Section: Methodsmentioning
confidence: 99%